Voluntary retirement and worker's welfare - Srinivasan, M.V. (1999)
The anxiety to modernise, restructure and globalise Indian industry is often leading to unnecessary retrenchment of workers. This is waste of precious labour force that could have been modernised through retraining. This article examines the voluntary retirement scheme and the national renewal fund which are designed to provide minimum sustenance security to the retired individual and his family. - Reproduced
Keywords: Labour - India; Labour